Alguns aspectos do puerpêrio de ovelhas da raça Santa inês. - Marcio Gianordoli Teixeira Gomes (2007)
During the puerperium uterine involution and the return of the reproductive activity occurs. The uterine involution is the rapid reduction of the uterus size accompanied by the non pregnant endometrium structure recovery. Factors that alter the uterine involution cause impact on the reproductive performance of the animals and considering the small number of works that studied the uterine involution in vivo on the Brazilian sheep breed, the present work aims to evaluate the uterine involution on the Santa Inês breed. So, followed by the cytology vaginal smears and the progesterone dosage, we evaluated the process of uterine involution by using ultrasonography, comparing, also, the effect of one and two lambes parturition, as well as the influence of nutritional restriction after 70 days of pregnancy on the uterine involution process. The work pointed out a larger period for the reduction and stabilization of the uterine size on the presence of two lambs and that the nutritional restriction of 15% on the maintenance energy seems to have no influence on the uterine involution process. However, we observed that ewes submitted to nutritional restriction calved slighted lambs. The first detected luteal functions occurred around the 45 day after calving. The ultrasonography method was of great utility on the evaluation of the uterine involution process, while the cytology vaginal smears exam was not adequate to characterize the evolution of the involution period of the genital system on the after calving. Keywords: ewes; puerperium; uterine involution